Longitudinal Modeling of Adolescents' Activity Involvement, Problem Peer Associations, and Youth Smoking - Metzger, Aaron (2011)
Longitudinal associations among different types of organized activity involvement, problem peer associations, and cigarette smoking were examined in a sample of 1,040 adolescents (mean age = 15.62 at baseline, 16.89 at 15-month assessment, 17.59 at 24 months) enriched for smoking experimentation (83% had tried smoking). A structural equation model tested longitudinal paths between three categories of involvement (team sports, school clubs and activities, and religious activities, measured at baseline and 15 months), problem peer associations (baseline and 15 months), and cigarette smoking behavior (baseline and 24 months). Multi-group analyses indicated pathways differed by type of activity and adolescent gender. Boys’ baseline team sports and religious involvement predicted lower levels of smoking at 24 months via continued activity involvement at 15 months. Girls’ involvement in school clubs and activities and religious activities indirectly predicted lower levels of smoking at 24 months via reduced exposure to problem peers at 15 months.